Improving the nutritional value and extending shelf life of red guava by adding calcium chloride - Ribeiro, Luiza Rocha [UNESP]; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevedo [UNESP]; Garcia, Emerson Loli [UNESP]; Leonel, Magali [UNESP]; Monteiro, Laís Naiara Honorato [UNESP]; Silva, Marcelo de Souza [UNESP]; Ferreira, Rafael Bibiano [UNESP] (Elsevier, 2020)
The high nutritional value of guavas is much appreciated and valued by consumers but extending the shelf life of these fruits is one of the most crucial factors to increase their commercialization. The present study aimed to evaluate the effects of the pre-harvest application of calcium chloride (0, 0.5, 1.0, 1.5, and 2%) on guava fruits and to evaluate the quality characteristics of the fruits during storage (0, 2, 4, and 6 days). The results showed that the pre-harvest sprays of 1.0% CaCl2 led to an increase in the levels of calcium in the fruits (0.82 g kg−1). The application of 1.0% CaCl2 also promoted 40% increase in ascorbic acid content after harvest (196.5 mg 100 g−1). The lowest weight loss and rot incidence occurred at 1.0% CaCl2. In addition, there was a decrease in the action of pectinmethylesterase and polygalacturonase in storage. Thus, the pre-harvest application of 1.0% CaCl2 in the red guava can preserve the quality of the fruit and increase the nutritional value.
Keywords: Ascorbic acid; Pectinmethylesterase; Polygalacturonase; Psidium guajava L.; Rots